Experimental investigations on the interfacial characteristics of steam-air mixture sonic jets in subcooled water. (December 2019) - Li, Weichao; Sun, Zhongning; Meng, Zhaoming; Fan, Guangming; Wang, Jianjun
Highlights: Four typical interfacial shapes are observed. The spreading rate of interfacial radius is in the range of 0.12–0.27. The interfacial fluctuation height is proportional to the axial position with spreading coefficient 0.03 ± 0.008. The maximum velocity and acceleration of interface fluctuation are estimated to be around 6 m/s and 20, 000 m/s 2, respectively. Abstract: Interfacial characteristics of steam-air mixture sonic jets are recorded and processed using image processing technique. Interfacial shape, radius, fluctuation height, fluctuation velocity and fluctuation acceleration are analyzed. Four typical interfacial shapes including expansion-contraction, double expansion-contraction, expansion-contraction-divergence and expansion-divergence are observed and a three-dimensional interfacial shape map is developed. Gas dynamic effect is notable in the axial region of the near field. The interfacial radius increases linearly with the axial distance in the far field. The spreading rate increases with the rise of air mass fraction and its value is in the range of 0.12–0.27. The interfacial fluctuation height is proportional to the axial distance both in the near field and far field. The spreading coefficient is in the range of 0.03 ± 0.008. In general, both interfacial fluctuation velocity and acceleration increase with the axial distance. The growth rate decreases rapidly in the near field and then increases slightly again in the far field. The maximum velocity and acceleration of interface fluctuation are estimated to be around 6 m/s and 20, 000 m/s 2, respectively.